The Influence of Intangible Assets, Financial Flexibility, and Human Capital on Sustainable Growth with Green Innovation as a Moderator - Purna, Putu Inten Citrawati; Werastuti, Desak Nyoman Sri; Adiputra, I Made Pradana (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study, titled "The Influence of Intangible Assets, Financial Flexibility, and Human Capital on Sustainable Growth with Green Innovation as a Moderator," aims to analyze the effects of intangible assets, financial flexibility, and human capital on sustainable growth within energy sector companies in Indonesia, with green innovation serving as a moderating variable. The research is driven by the challenges faced by the energy sector, such as climate change, resource scarcity, and the transition to renewable energy. A quantitative approach was applied, utilizing secondary data from financial reports of energy companies listed on the Indonesia Stock Exchange during the 2020–2023 period, analyzed using STATA software. The findings indicate that intangible assets have no significant effect on sustainable growth, whereas financial flexibility and human capital show positive and significant impacts. Additionally, green innovation strengthens the relationship between the three variables and sustainable growth. This research is expected to provide valuable insights for the development of sustainable business strategies in the energy sector.